Biopsychosocial Dimensions of Perinatal Anxiety in Primigravida Women at Primary Health Care: A Mixed Method Study - Dea Pebrianti; Dyah Ayu Utari; Ismarwati; Cesa Septiana Pratiwi (Journal of Health Sciences and Medical Development, 2026)
Perinatal anxiety among primigravida women is a significant yet frequently overlooked maternal mental health concern. This study analyzed the biopsychosocial dimensions of perinatal anxiety among primigravida women in primary health care settings using a sequential explanatory mixed methods design. The quantitative phase involved 171 primigravida women recruited through stratified proportional random sampling from two primary health care centers, who completed the Perinatal Anxiety Screening Scale (PASS). The qualitative phase included 15 informants with anxiety scores above 21 who participated in in-depth interviews. Quantitative data were analyzed using Chi-Square tests, while qualitative data were processed through NVivo 12 Plus following the Miles and Huberman framework. Ethical clearance was obtained from the Research Ethics Committee of Universitas 'Aisyiyah Yogyakarta (No. 1453/KEP-UNISA/IV/2022). The results showed that 39.2% of respondents experienced anxiety (17.5% mild, 18.7% moderate, and 2.9% severe), with a significant association between gestational trimester and anxiety level (p = 0.041). The second trimester exhibited the highest proportion of anxiety at 56.0%. Qualitative analysis revealed three themes: forms of maternal discomfort, antenatal care access experiences, and biopsychosocial dimensions of anxiety encompassing biological, psychological, socioeconomic, environmental, and social support factors. Pearson correlation identified psychological factors (r = 0.95) and social support (r = 0.85) as dominant determinants. The biopsychosocial model proved effective as a comprehensive framework for understanding perinatal anxiety in primary care. These findings provide an evidence-based foundation for holistic maternal mental health interventions and underscore the necessity of routine anxiety screening, strengthened counseling services, and structured social support programs within antenatal care.